2007
DOI: 10.1681/asn.2006070738
|View full text |Cite
|
Sign up to set email alerts
|

What Predicts Progression and Regression of Urinary Albumin Excretion in the Nondiabetic Population?

Abstract: An increase or decrease in urinary albumin excretion (UAE) is associated with, respectively, a higher or lower risk for renal and cardiovascular disease, independent of widely known cardiovascular risk factors. This study aimed to identify factors that are associated with changes in UAE in the nondiabetic population using data of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
2
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 41 publications
0
26
2
8
Order By: Relevance
“…9,10,35 Most of these studies did not adjust for other cardiovascular risk factors, but in two population-based studies in persons without diabetes, increased FG in men and HbAR 1c R in both genders were found to be independent predictors of increased urinary albumin excretion. 22,36 However, neither of these studies excluded persons with diabetes at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,35 Most of these studies did not adjust for other cardiovascular risk factors, but in two population-based studies in persons without diabetes, increased FG in men and HbAR 1c R in both genders were found to be independent predictors of increased urinary albumin excretion. 22,36 However, neither of these studies excluded persons with diabetes at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…14 It has been shown in populations with diabetes and hypertension that these changes, whether spontaneous or medication induced, are associated with a parallel change in risk for CV disease. 6,7,[15][16][17] In analogy, when we looked at our communitybased study population, changes in UAE were associated with parallel changes in CV risk.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, such changes were found to be associated with a significant parallel change in CV risk in our study. Because it is estimated that in the general population after approximately 4 yr of follow-up the incidence of progression is approximately 10%, 14 this suggested that by repeating the UAE measurement, a substantial number of individuals with an increased CV risk can be detected.…”
Section: Discussionmentioning
confidence: 99%
“…ÕÇÍ ó äèòÿ÷îìó â³ö³ ñïðè÷èíÿþòü àíîìà볿 ðîçâèòêó (âðîäaeåí³ àíîìà볿 íèðîê ³ ñå÷î-âèâ³äíèõ øëÿõ³â), ôîêàëüíî-ñåãìåíòàðíèé ãëîìåðóëîñêëåðîç (ÔÑÃÑ), ãåìîë³òèêî-óðåì³÷íèé ñèíäðîì (ÃÓÑ), ³ìóííî-êîìïëåêñí³ çàõâîðþâàí-íÿ ³ ñïàäêîâ³ íåôðîïàò³¿, òàê³, ÿê õâîðîáà Àëüïîðòà [2,7]. Çàãàëüíèì ïàòîìîðôîëîã³÷íèì ðåçóëüòàòîì, ùî ñòîñóºòüñÿ ïîøêîäaeåííÿ íèðîê ïðè ÕÇÍ, º ãëîìåðóëîñêëåðîç, ñêëåðîç ñóäèí, òóáóëî-³íòåðñòèö³éíèé ô³áðîç.…”
Section: ïîðóøåííÿ â ñèñòåì³ êîíòðîëþ àïîïòîçó ïðè õðîí³÷íîìó ãëîìåðóunclassified
“…Íà íàñòóïíèõ äîñë³äaeóâàíèõ ñòàä³ÿõ òàêîae ñïîñòåð³ãà-ëîñÿ ³íã³áóâàííÿ Na + , K + -ÀÒÔàçè çà âïëèâó äaeåðåëà ì³êðîõâèëüîâîãî âèïðîì³íþâàííÿ â ðåaeèì³ î÷³êóâàííÿ. Çì³íè, éìîâ³ðíî, ïîâ'ÿçàí³ ç òèì, ùî íà öèõ åòàïàõ ðîçâèòêó â³äáóâàºòüñÿ äåñèíõðîí³çàö³ÿ ïîä³ëó çàðîäêîâèõ êë³òèí, ùî ìîaeå ïðèçâåñòè äî àâòîíîì³çàö³¿ ìåòàáîë³÷íèõ ïðîöåñ³â [2].…”
unclassified